Expression data from primary culture human myometrial cells - Lei,K; Sooranna,SR; Johnson,MR (Genomics Data, 2015)
Inflammation plays a central role in many human diseases. Human parturition also resembles an inflammatory reaction, where progesterone (P4) and progesterone receptors (PRs) have already been demonstrated to suppress contraction-associated gene expression. In our previous studies, we have found that the progesterone actions, including progesterone-induced gene expression and progesterone's anti-inflammatory effect, are mediated by PR, GR or both. In this study, we used microarrays (GSE68171) to find P4 and IL-1β responsive genes and IL-1β responsive genes which were repressed by P4. These data may provide a broader view of gene networks and cellular functions regulated by P4 and IL-1β in human myometrial cells. These data will also help us understand the role of PR and GR in human parturition.